Behavioral economics and safe sex: Examining condom use decisions from a reinforcer pathology framework. Issue 2 (5th July 2021) - Harsin, Joshua D.; Gelino, Brett W.; Strickland, Justin C.; Johnson, Matthew W.; Berry, Meredith S.; Reed, Derek D.
Abstract : Condom use substantially reduces unwanted pregnancies and sexually transmitted infections. While condom availability is a significant public health priority, effects of condom availability constraints remain relatively under‐researched. The limited research on condom availability suggests two major barriers to use: (1) effort/costs and (2) delay to access. To date, we are aware of no study that explores both demand for and discounting of condom availability; the focus of this study was to account for condom decisions using a reinforcement pathology framework. This study used a condom purchase task and the Sexual Delay Discounting Task to quantify behavioral economics of condom use. Low sexual discounting was associated with higher willingness to engage unprotected sex. Demand metrics suggest participants indicating abstinence at condom breakpoint were willing to pay nearly double for condoms relative to individuals indicating unprotected sex at breakpoint. Finally, we grouped participants into reinforcement pathology risk groups based on their discounting and demand indices; these groups significantly differed in self‐reported number of sexual partners, unprotected sexual partners, and Sexual Desire scores. This study demonstrates the value of behavioral economic approaches to public health concerns, and further underscores the translational benefits of quantitative metrics to shed novel light on risky health decisions.